21st Century Skills and Industrial Design Education: A Theoretical Approach and Comparative Analysis of Educational Programs - Sevindik, Tuncay; Irmak, Yavuz; Ekinci, Sinem (Fırat University, 2026)
This study aims to analyze the extent to which cognitive competencies defined as 21st century skills namely critical thinking, creativity, problem solving, and metacognitive awareness are integrated into undergraduate-level industrial design education processes. The theoretical framework of the research is grounded in constructivist learning theory, experiential learning models, and personalized learning approaches. A pedagogical analysis has been conducted based on the perspectives of prominent theorists such as Piaget, Vygotsky, Kolb, and Bloom. A comparative methodology was employed focusing on the cases of Italy, Germany, and Türkiye. Curriculum structures, pedagogical strategies, university–industry collaborations, and learning outcomes were examined from a multidimensional perspective. The findings reveal that Germany, through its applied sciences-oriented approach, systematically develops problem-solving and metacognitive skills; Italy emphasizes personal expression and aesthetic sensitivity through its creativity-based educational model; whereas Türkiye, although displaying a hybrid structure influenced by both models, faces structural limitations in pedagogical integration and assessment mechanisms. In conclusion, the study finds that the development of 21st century skills relies not only on student-centered approaches but also significantly on teacher guidance, the flexibility of learning environments, and the establishment of integrated structures with industry. Industrial design education can only cultivate creative and solution-oriented individuals when these multilayered components are effectively and coherently structured.

This study aims to analyse the extent to which cognitive competencies defined as 21st century skills, such as critical thinking, creativity, problem solving, and metacognitive awareness, are integrated into undergraduate education processes in Industrial Design Education. The theoretical framework is based on constructivist learning theory, experiential learning models, and individualised learning approaches; a pedagogical analysis was conducted based on the approaches of leading theorists such as Piaget, Vygotsky, Kolb, and Bloom. A comparative method was followed in the study in the context of Italy, Germany, and Turkey; curriculum structures, pedagogical strategies, relationships established with the sector, and learning outcomes were examined in a multidimensional manner. In the findings section: Germany's applied sciences-based approach systematically develops problem-solving and metacognitive skills, Italy's creativity-based education model prioritises individual expression and aesthetic sensitivity, and Turkey has a hybrid structure between these two models but has structural limitations in pedagogical integration and evaluation mechanisms. In conclusion, it has been observed that student-centred approaches alone are not decisive in imparting 21st-century skills; rather, teacher guidance, the flexibility of learning environments, and sector-integrated structures are decisive factors.
21. YÜZYIL BECERİLERİ VE ENDÜSTRİYEL TASARIM EĞİTİMİ: KURAMSAL YAKLAŞIMLAR VE EĞİTİM PROGRAMLARI ÜZERİNE KARŞILAŞTIRMALI BİR ANALİZ
Keywords: Educational Psychology; Eğitim Psikolojisi; Applied and Developmental Psychology (Other); Uygulamalı ve Gelişimsel Psikoloji (Diğer)